Cơ hội và thách thức đối với đội ngũ trí thức khoa học xã hội và nhân văn Việt Nam trong sự nghiệp đổi mới ở nước ta hiện nay - Phượng, Ngô Thị (VNU Journal of Science: Social Sciences and Humanities, 2004)
The work analyzed opportunities for intellectual’s of social sciences and humanities in Vietnam nowadays: Communist ParV, State and country connerned and gave much condictions for creative labour of social sciences and humanities of Vietnam; artive pratice and great achievement or renewal work is good circumstance and important basis for developping role of its; the element of age effected actively on its. Another way, intelletual's circles of Vietnammese social sciences and humanities also copes with a lot of challenges such as: the more heavy responsibility of its; the difficulties inside country and the complicated questions of the World, which are effecting on it; the limitation on quanlity, quality, structure of its. However, opportunities can become challenges and constrast to. The work also shows some ways, which intelletual’s circles of Vietnammese social sciences and humanities can use opportunities and pass challenges to more cotribute on renewal work of country.